Nivel de conocimiento y su relación con las prácticas de prevención del cáncer de cuello uterino en mujeres en edad fértil del Caserío Bello Horizonte- Banda de Shilcayo. Periodo Julio-Setiembre 2014 - Mera Alvarado, Ana Patricia (2014)
This study's main objective was to determine the level of knowledge And practices regarding prevention of cervical cancer in women of Childbearing age Bello Horizonte hamlet Shilcayo, July-September 2014. A Descriptive study was conducted, prospective, correlational, cross-sectional; the Sample consisted of 102 women of childbearing age who met the inclusion and Exclusion criteria, probabilistically derived 95% confidence. To measure the Variable level of knowledge the questionnaire consisted of 13 closed questions, Classified into low, intermediate, high being the maximum score 26 points. To Measure the variable practice of preventing cervical cancer, a Questionnaire test assessed the scale of Likert amended, which consisted Of fourteen questions that expose the practices undertaken by women of childbearing Age hamlet Bello Horizonte was applied to prevent cervical cancer. The Results were: 35.3% of women of childbearing age are in the age group 31- 40 years; 55.9% were cohabiting; 52.9% had secondary education; and 85.3% are Housewives. 52.9% of women of childbearing age have medium level of knowledge About prevention of cervical cancer. 62.7% of women of childbearing age have good Practices on prevention of cervical cancer. In the confirmation of the Hypothesis score p = 0.014 demonstrating that there is a statistically significant Relationship (p ≤ 0.05) between the average level of knowledge and Practical prevention of cervical cancer in women age was Obtained Bello Horizonte fertile hamlet La Shilcayo.